Student Management in Improving the Quality of Education in SMK Negeri 2 Toraja Utara - Oce Payung Limbong; Hotmaulina Sihotang; Witarsa Tambunan (Budapest International Research and Critics University, 2022)
This study aims to analyze: 1) the implementation of student management in improving students' hard skills; 2) the implementation of student management in improving students' soft skills; 3) To analyze student management efforts to improve quality; 4) supporting and inhibiting student management factors 5) efforts to overcome student management barriers in improving the quality of education The method used in this research is the descriptive qualitative research method. The data collection technique is done through observation, interviews, and documentation. The data were analyzed utilizing data reduction, data presentation (data display), and concluding. From the results of this study it can be concluded that: a) student management plans, implements, monitors and evaluates activities to improve students' hard skills b) student management plans, implements, monitors and evaluates activities that can improve students' soft skills 3) student management efforts in improving quality education, among others a) self-development through routine school activities, spontaneous activities, exemplary and conditioning; b) integrating the values of the nation's character in the syllabus and lesson plans; c) application of rules, norms, morals, and ethics that apply in schools; 4) The supporting factors of student management in improving the quality of education are educators who have good qualifications, facilities and infrastructure, the inhibiting factors are that understanding is not yet real, funds are not adequate, student motivation is still low, exemplary needs to be improved; 5) Student management efforts in overcoming any obstacles that occur, among others 1) build communication with all school parties; 2) establish communication with parents; 3) teachers always provide motivation, enthusiasm and appreciation for students who excel; 4) provide training for each teacher.